Long Workweeks and Strange Hours - Daniel S. Hamermesh; Elena G. F. Stancanelli (Institute for the Study of Labor (IZA), 2014)
American workweeks are long compared to other rich countries'. Much less well-known is that Americans are more likely to work at night and on weekends. We examine the relationship between these two phenomena using the American Time Use Survey and time-diary data from 5 other countries. Adjusting for demographic differences, Americans' incidence of night and weekend work would drop by about 10 percent if European workweeks prevailed. Even if no Americans worked long hours, the incidence of unusual work times in the U.S. would far exceed those in continental Europe.
Keywords: J22; J08; 330; night work; weekend work; shorter hours